How understanding the factors of visual perception proposed by Bloomer can contribute to the representation of photographs - Gislene Rodrigues da Silva; Célia da Consolação Dias (Documentación de las Ciencias de la Información, 2024)
Visual perception is a field of knowledge belonging to Cognitive Psychology. It was realized that such knowledge could contribute to the indexing of photographs based on the understanding of human cognition processes to identify how the individual interprets and their visual perception of a photograph. This understanding helps to establish criteria for selecting keywords for indexing photographs. This research presents Bloomer's (1990) visual perception factors and reflects on the literature review of how such studies can contribute to indexing photographs. As a result, two points stand out: visual perception can contribute to organizing more efficient and intuitive online photography catalogues, providing users with a better experience and ease in retrieving visual content, and finally, it can help information professionals select terms relevant to users.